ANALISIS PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. BANK MANDIRI (PERSERO) Tbk. CABANG KOLAKA - Syarmila Syarmila; Nurwati Nurwati; Yusuf Montundu; Muhammad Masri; Hastuti Hastuti (Jurnal Manajemen dan Kewirausahaan, 2022)
This study aims to analyze the effect of compensation and work motivation on employee performance at PT. Bank Mandiri (Persero) Tbk. Kolaka Branch. The research design when viewed from the data collection method is survey research, when viewed from the analysis objectives, this research is explanatory research. Data collection was done by using a questionnaire. Data obtained from 47 respondents. Data analysis used the Standardize Multiple Linear Regression Analysis model. The results, indicating that the correlation between the variables of compensation and work motivation on employee performance is quite strong. Based on the results of the analysis, it can be concluded that compensation and work motivation simultaneously have a positive and significant effect on employee performance. Compensation has a positive and significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. From the conclusions above, it is recommended for the Bank to consider the results of this study, namely if the compensation and work motivation increase can improve employee performance.